Hepatorenal Syndrome - Pınar Zeyneloğlu (Galenos Yayinevi, 2012)
Renal failure is a common major complication in patients with advanced cirrhosis and generally indicates a poor prognosis when combined with liver failure. Hepatorenal syndrome (HRS) is characterised by a combination of disturbances in circulatory and kidney function. Arterial pressure is decreased in the systemic circulation due to reduced total systemic vascular resistance. Kidney dysfunction is caused by reduction in renal blood flow. The diagnosis of HRS is based on exclusion of other disorders that cause acute kidney injury in cirrhosis as there are no specific tests. There are two types of HRS with different characteristics and prognostics. Liver transplantation is the treatment of choice for all patients without contraindication. The best approach to the pharmacologic management is the administration vasoconstrictor drugs based on the pathogenesis. Many vasoconstrictors including vasopressin analogues (terlipressin, ornipressin and vasopressin), somatostatin analogues (octreotide) and alpha-adrenergic analogues (midodrine and norepinephrine) have been studied. In most of the studies intravenous albumin therapy was coadministered with vasoconstrictor drugs and suggested that albumin should be considered as the component of pharmacologic intervention in patients with HRS. Renal replacement therapy in the form of hemodialysis or continuous venovenous hemofiltration has been used in the management of HRS patients awaiting transplantation or in those with acute potentially reversible conditions. The artificial hepatic support systems require further investigation. (Journal of the Turkish Society Intensive Care 2012; 10: 37-44)